Sequence analysis of the N-acetyltransferase 2 gene (NAT2) among Jordanian volunteers. Issue 1 (1st January 2018) - Jarrar, Yazun Bashir; Balasmeh, Ayat Ahmed; Jarrar, Wassan
ABSTRACT: The present study aimed to identify the NAT2 haplotypes, linkage disequilibrium, and novel NAT2 genetic variants among Jordanian population. We isolated the genomic DNA from 68 healthy, Arab, unrelated Jordanian volunteers to amplify the protein-coding region of NAT2 gene by polymerase chain reaction (PCR). Then, the amplified PCR products were sequenced using Applied Biosystems Model (ABI3730x1). It is found that the allele frequencies of known NAT2 genetic variants 191G>A, 282C>T, 341T>C, 481C>T, 590G>A, and 803A>G were 0.7, 26.5, 48.5, 35.3, 30.9, and 32.4%, respectively. The NAT2 allele frequencies were generally similar to those of white Europeans but different from those of Asian and African populations. The most common NAT2 haplotype was NAT2*5B with a frequency of 29.3%. According to the NAT2 haplotype frequencies, 72% (95% confidence interval 61.4–82.7%) of the volunteers were slow encoding NAT2 haplotype acetylators. The NAT2*5 represented variants 341T>C and 481C>T were in strong but not complete linkage disequilibrium ( D ′ = 0.8, r 2  = 0.63). In addition, this study found a novel nonsynonymous NAT2 436G>A genetic variant with low frequency (0.7%). However, this novel variant was predicted to be tolerated and not harmful to the NAT2 protein, using in silico prediction tools. It is concluded that the frequency of slow encoding NAT2 haplotype was high among Jordanian volunteers, which may have effects on drug responses and susceptibility to some diseases, such as cancers.